Primary Varicella Pneumonia in an Adult With Robust Immune Status: A Case Report - Sunil Bhatta; Sukriti Pandit; Pratik Chaudhary (Clinical Case Reports)
ABSTRACT Primary varicella‐zoster virus (VZV) infection is infrequent in adults, but it causes more than 10 to 20 times the morbidity and mortality seen in healthy children and pneumonia being the most prevalent consequence. Early recognition and aggressive management of primary varicella pneumonia with antiviral therapy and supportive care is essential to prevent severe complications such as acute respiratory distress syndrome (ARDS).